2008
DOI: 10.1530/eje-07-0822
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of atherogenic proteins neutrophil gelatinase-associated lipocalin and its complex with matrix metalloproteinase-9 are significantly lower in women with polycystic ovary syndrome: hint of a protective mechanism?

Abstract: Background: Neutrophil gelatinase-associated lipocalin (NGAL) and matrix metalloproteinase-9 (MMP-9) have been considered as important mediators of vascular remodeling and plaque instability. The formation of a complex with NGAL and MMP-9 is crucial for atherotic plaque erosion and thrombus formation. In women with polycystic ovary syndrome (PCOS), the incidence of cardiovascular clinical events is not increased, despite the fact that they display a wide spectrum of risk factors. Since the instability of ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
(32 reference statements)
1
29
1
2
Order By: Relevance
“…While increased levels of MMP2 and/or MMP9 have shown in PCOS patients (Lewandowski et al 2006, Liu et al 2007, no significant differences have been observed between PCOS and control in the study by Gomes et al (2011), or a reduced MMP9 level has been reported by Diamanti-Kandarakis et al (2008). Similar conflicting results are also available about serum TIMP1 and TIMP2 levels (Lewandowski et al 2006, Liu et al 2008, Gomes et al 2011.…”
Section: Introductionmentioning
confidence: 85%
“…While increased levels of MMP2 and/or MMP9 have shown in PCOS patients (Lewandowski et al 2006, Liu et al 2007, no significant differences have been observed between PCOS and control in the study by Gomes et al (2011), or a reduced MMP9 level has been reported by Diamanti-Kandarakis et al (2008). Similar conflicting results are also available about serum TIMP1 and TIMP2 levels (Lewandowski et al 2006, Liu et al 2008, Gomes et al 2011.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, lipocalin-2 was not associated with cardiovascular risk indicators as defined by echocardiographic examination [10]. Diamanti-Kandarakis et al demonstrated that circulating lipocalin-2 levels were significantly lower in women with PCOS and were not associated with obesity, insulin resistance, and estradiol concentrations [3]. Although women with PCOS have numerous risk factors that can cause cardiovascular disease, it was reported that the incidence of cardiovascular events was not elevated in PCOS [29].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Although women with PCOS have numerous risk factors that can cause cardiovascular disease, it was reported that the incidence of cardiovascular events was not elevated in PCOS [29]. Therefore, the results of Diamanti-Kandarakis highlighted that lipocalin-2 is related to cardiovascular events rather than atherosclerotic heart disease; lipocalin-2 may have a protective role in PCOS [3,10].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 2 more Smart Citations